Chromonychia Secondary to Chemotherapy - Marien Lopes; Clarice Jordão; Rachel Grynszpan; Celso Sodré; Marcia Ramos- (Karger Publishers, 2013)
Chemotherapy drugs can affect the skin and its appendages. Several clinical presentations can be observed, depending on the affected structure. The most common dermatological side effect is chromonychia. The main causative agents are: (1) cyclophosphamide, which can provoke a diffuse, black pigmentation, longitudinal striae and dark grey pigmentation located proximally on the nails; (2) doxorubicin, which promotes dark brown bands alternating with white striae and dark brown pigmentation in transverse bands, and (3) hydroxyurea, which produces a distal, diffuse, dark brown pigmentation. In the majority of cases, the effects are reversible after the suspension of the causative agent for a few months. We report a patient who developed chromonychia while undergoing treatment with cyclophosphamide, vincristine, doxorubicin, dexamethasone, methotrexate and cytarabine for acute lymphocytic leukemia.